Pengaruh Kualitas Pelayanan, Produk Dan Strategi Promosi Terhadap Kepuasan Nasabah Menabung Di Bank Syariah Indonesia KCP Jakabaring - Aprija Rosianti; Hilda Hilda; Syamsiar Zahrani (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to determine the effect of service quality,product and promotional strategies on customer satisfaction in saving at Bank Syariah Indonesia KCP Jakabaring. the variables in this study are sevice quality (X1),Products (X2),Promotion strategy (X3),while the dependent variable in this study is customer satisfaction (Y). The population in this study were all customers of Bank Syariah Indonesia KCP Jakabaring. The sample was 100 customers using the Lemeshow formula and using incidental sampling techniques. The data used is primary data. The data analysis technique in this research uses IBM SPSS version 26, which consists of the classic assumption test, multiple linear regression test, and hypothesis test. The ressults of this study were obtained from the t-test and f-test which showed thar the variables of service quality,products and promotional strategis had an eeffect on customer satisfaction partially and simultaneously.the determination coefficient test (R2) obtained data results of 54.5% which were explained by service quality,product and promotional strategies, while the remaining 45.5% were explained by other variables outside the study